2011
DOI: 10.1007/s10681-011-0533-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of intersubgenomic heterosis in Brassica napus carrying genomic components of B. rapa

Abstract: Although strong intersubgenomic heterosis for seed production has been observed between ''natural'' domesticated Brassica napus (rapeseed, AACC) and a new type of rapeseed into which subgenomic components of Brassica rapa (AA) have been introgressed, the molecular genetic mechanism of this intersubgenomic heterosis is not understood. In this study, a recombinant inbred line population of new type rapeseed derived from a cross between B. napus and B. rapa, together with a population from a backcross with the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…To this end, major effort has been put towards exploring and utilizing subgenomic variation within each of the Brassica A, B and C subgenomes and between species for B. napus crop improvement. Both targeted gene transfer and whole-genome introgressions into B. napus have been carried out via interspecific crosses, significantly broadening the genetic base of B. napus and promoting trait improvement and hybrid heterosis (Becker et al, 1995;Chatterjee et al, 2015;Chen et al, 2010;Fu et al, 2012;Li et al, 2014b;Rahman, 2001;Schranz and Osborn, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, major effort has been put towards exploring and utilizing subgenomic variation within each of the Brassica A, B and C subgenomes and between species for B. napus crop improvement. Both targeted gene transfer and whole-genome introgressions into B. napus have been carried out via interspecific crosses, significantly broadening the genetic base of B. napus and promoting trait improvement and hybrid heterosis (Becker et al, 1995;Chatterjee et al, 2015;Chen et al, 2010;Fu et al, 2012;Li et al, 2014b;Rahman, 2001;Schranz and Osborn, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, most of the studies conducted to date to evaluate different gene pools of Brassica for the improvement of spring or winter or semi-winter B. napus were focused on either the use of spring B. napus for spring type hybrid (Grant and Beversdorf, 1985;Brandle and McVetty, 1990;Engqvist and Becker, 1991;Diers et al, 1996;Cuthbert et al, 2009), or the use of winter or semi-winter B. napus for spring type hybrid (Butruille et al, 1999;Udall et al, 2004;Quijada et al, 2004Quijada et al, , 2006Qian et al, 2007;Kramer et al, 2009), or the use of winter or semi-winter B. napus for winter type hybrid (Lefort-Buson et al, 1987;Qian et al, 2009), or the use of the allied species for winter or semiwinter (Gehringer et al, 2007;Radoev et al, 2008;Zou et al, 2010;Fu et al, 2012;Girke et al, 2012;Li et al, 2014) or spring Seyis et al, 2006) type of hybrid. However, so far, no study has been conducted to compare the value of different gene pools for increasing the level of heterosis and seed yield in spring B. napus hybrid canola.…”
mentioning
confidence: 99%
“…Interspecific hybridization in Brassica can induce a number of genetic change in the genome through homoeologous recombination between the chromosomes (Udall et al, 2005;Leflon et al, 2006;Zou et al, 2011) and this can create new genetic variation and exert significant effect on seed yield (Zou et al, 2011;Fu et al, 2012). While working with B. napus × B. rapa interspecific cross, Fu et al (2012) found that the novel alleles generated in the progeny of this interspecific cross can contribute to heterosis for seed yield in B. napus through allelic and non-allelic interactions. Zou et al (2010) found improved agronomic performance and strong heterosis for seed yield in hybrids of natural B. napus and B. napus lines carrying A and C genome contents introgressed from B. rapa and B. carinata, respectively.…”
Section: Discussionmentioning
confidence: 99%